Linking ages in migration research: a critical approach to left-behindness in childhood and old age - Azevedo, L.; Anne Carolina (22nd IMISCOE Annual Conference, 2025)
The literature on left-behind individuals very often focuses on children and older adults who stay in the country of origin in a context of economic migration of parents (if the focus is children) or children (if the focus is older adults). Thus, both children and older people are constructed as vulnerable in the agentic process of migration of the middle generation. Although children and older people might experience similar aspects when they are ‘left-behind’, migration scholars tend to focus on either childhood or old age, and rarely interact with one another, with scholars, but also disciplines remaining isolated in their theoretical and empirical perspectives (see Wanka et al., 2024). Moreover, children and older people are often seen as those who stay, rather than those who might leave others behind. In this paper, we reverse this view and bring together two different projects – one with Ukrainian refugee children in Switzerland and one with older Portuguese migrants in Switzerland and Portugal – to explore similarities and differences in their relationship with the family members ‘they have left behind’. By adopting a transnational family well-being lens to look to these relations, in which practical, emotional, and financial transnational care relations take place, we show that those who ‘stayed behind’ were not necessarily ‘left behind’ by those who migrated. Thus, by bridging the research on the two extremities of the life course we put into question the widespread concept of ‘left-behind’, strongly used in research on migration related to both childhood and ageing